(untitled) (CIPEEX, 2025)
This study addresses the right to the city, urban mobility, and public road infrastructure, highlighting the importance of these factors for sustainable urban development. With the accelerated growth of Brazilian cities, efficient management of public roads has become essential to ensure equal access to urban services and improve quality of life. The research focuses on Avenida João Leite, in Goiânia-GO, with the main objective of analyzing the urban development policies applied in this region, seeking to understand the challenges and advances in the implementation of legal planning guidelines. Among the specific objectives, the study proposes to: a) Examine the evolution of legal and constitutional guidelines for urban development in Brazil; b) Investigate the historical and legal perspectives of urban planning in Goiânia, with an emphasis on the Santa Genoveva neighborhood; c) Analyze the practical application of these policies on Avenida João Leite, evaluating infrastructure, accessibility, and the impact on residents’ quality of life. The methodology employed includes bibliographical, qualitative, empirical, and documentary research. The relevance of the topic is justified by the need to improve mobility and urban infrastructure to promote more inclusive and sustainable cities, especially in fast-growing regions like Goiânia. The results revealed that although significant progress has been made in implementing urban development policies, challenges remain, especially in relation to infrastructure and accessibility. The application of urban planning guidelines on Avenida João Leite has brought improvements in mobility and quality of life, but the full solution to the problems identified depends on greater investment and more efficient management. In conclusion, the study shows that, despite progress, Avenida João Leite still faces challenges in achieving full urban sustainability. The policies implemented have been effective to a certain extent, but in order to transform the Avenue into a model of sustainability, it is necessary to tackle more directly the remaining problems, such as inadequate accessibility and infrastructure maintenance.